Disturbance Observer-Based Motion Control For A Simple Direct Drive System - Hasim, Norhaslinda; Chong, Shin Horng; Khor, Hooi Khee (Penerbit Universiti, UTeM, 2016)
Direct drive system is the driving part that is directly connected to the driven part without using a gearbox. The advantages of direct drive system are frictionless, high efficiency, noise reduction and high torque, produced at low speed. However, the direct drive motor system has its limitation, which is sensitive to the disturbance and parameter variation. In this paper, a proportional derivative controller with disturbance observer (PDDO) is designed to achieve high positioning performance of the direct-drive system in the presence of mass and disturbance force variations. The direct-drive system in this paper is driven using voice coil motor. The disturbance observer controller is relatively easier to design than the other advanced controllers and often shows higher robust to the disturbance force and model parameter change, as compared to the conventional controller. The positioning performance of PDDO controller is evaluated and compared with a PID controller, which is designed to have similar sensitivity as the PDDO control. The positioning performance of the controllers is examined in the presence of different mass and disturbance force. Overall, the PDDO has demonstrated better robust performance as compared to the PID controller.